Korelasi Komponen Visual, Auditorial, Dan Kinestetik Dari Gaya Belajar Dengan Prestasi Belajar Matematika Siswa - Lana Sugiarti -; St Suwarsono (UNIKA SANTU PAULUS RUTENG, 2019)
This research aims to (1) know wheter there is a correlation between the visual components of mathematics learning achievement of students (2) know whether there is a correlations between auditory component to student mathematics achievement (3) know whether there is a correlations between kinesthetic components of mathematics learning achievement of students. This research belongs to the correlations research with the quantitative data. The data was in the form of a visual component questionnaire score, auditorial component questionnaire component score, kinesthetic component questionnaire scores and student achievement test scores. This research made used of statistical interval data and data processor Inferential Parametris, by using Kolmogorov-Smirnov Normality Test and Product Moment Correlation Coefficient Test. The results of this research was that (1) there is not significant correlations between visual component with student mathematics achievement (correlations coefficient -0,265) (2) there is a significant correlations between auditory component with student mathematics achievement (correlations coefficient 0,661) (3) there is not significant correlations between kinesthetic component with student mathematics achievement (correlations coefficient -0,217).